STRUKTUR TEKS, KOGNISI DAN KONTEKS SOSIAL DALAM BERITA ONLINE MENGENAI PENGUSUNGAN GIBRAN SEBAGAI CAWAPRES - Yusi Yustisian Adlah; Agus Hamdani (LP2M UIN Abdul Muthalib Sangadji Ambon, 2023)
AbstractThis study adopts the theory of Critical Discourse Analysis by Teun A. van Dijk in evaluating online news articles published in two media, namely Kompas.com and detik.com, in order to explore the author's views and compare the views of both. The news topic chosen by the researcher was about